Analisis Kebijakan Pengentasan Kemiskinan di Kabupaten Brebes Melalui Pengembangan Industri - Reza Saputra, Umar (Program Studi Administrasi Publik Universitas Muhamamdiyah Bengkulu, 2021)
Poverty becomes the priority issued of development from several regions in reducing the poverty rate. The success and failure of development in reducing poverty can be seen from the poverty rate in a region. The purpose of this study is to provide an alternative policies in reducing poverty rate in Brebes District that it is accordance with the Local Government Regulation No 2 of 2018. Data BPS Showed that Brebes has the largest number of poor people in Central Java. It is amount 16,22%. So that Brebes ranked as the third poor district after Kebumen and Wonosobo. The suggestion for that policy has took by the assessment of alternatives policy. It is to maximize the One Village One Product (OVOP) Program. OVOP program regarded as a program that can encourage the community in creating a product and opening jobs for poor people so that it can fill their daily necessary